Optimization of parameters for the Fe-humic acid complex formation using flourescence spectroscopy. - Araniador, Glaicyl Dame Ann B.
Humic acid was extracted from an artesian well located at Sta. Barbara, Iloilo. It was black in color and had a powdery texture after oven-drying. Humic acid samples were used to prepare complexes with 〖Fe〗^(3+) ions to determine the ideal conditions to maximize the binding of the metal ion. Using the fluorescence data of the ligand as a comparative measure to confirm complex formation, varying concentration and pH conditions were used in preparing Fe-HA complexes. The excitation spectra of the different concentration ratios prepared showed that pH 6 favored the complex formation. The emission spectra showed that pH 6 exhibited high fluorescence signals. The EEMs of different concentration ratios at pH 6 showed that it is the optimal range for complex formation. In pH 8 and pH 10, no consistent pattern in their EEMs can be observed. This indicates that alkaline conditions, complex formation is not favored.